SWOT Analysis In Strategy Sales Call on Sales and Marketing Department At The Hotel All Seasons Jakarta Thamrin - Asmawih; Daniel Stephanus Limidy; Sahlan Toro; Tobaroni; Diyan Maulidasari (The Postgraduate School of Tourism Sahid Polytechnic, 2023)
Purpose: This research reviews the sales call strategy on the room occupancy rate at the All-Seasons Jakarta Thamrin. The process of this sales call has strengths, weaknesses from within, and opportunities and threats from outside, which are presented in the results of the SWOT data processing technique consisting of IFAS and EFAS Matrix. Based on the analysis, it is known that the position of All Seasons Jakarta Thamrin is currently in quadrant I, namely the part of the Growth strategy or aggressive growth, with an IFAS score of 1.09 and an EFAS score of 0.59. Thamrin Hotel. This research aims to discover the sales call strategy's strengths, weaknesses, opportunities, and threats. Research methods: This research uses a descriptive research method Qualitative. To answer the problems encountered by collecting data. This is done by describing or describing the data that has been collected. The process of determining the sample was carried out by using purposive sampling with four respondents who were taken randomly. The products offered are rooms, meeting packages, and products. The skills mastered are communication, Public Speaking, analytics, and negotiations to create win-win solutions between guests and hotels. Result and discussion: This research shows that the room occupancy rate sales call at Hotel All Seasons Jakarta Thamrin has good internal strength and opportunities externally to seize the existing market. Although it still requires more teams to support operations. Apart from having a millennial concept, this hotel is also located in a strategic business district, department stores, and tourist attractions in downtown Jakarta. Prices negotiated during sales call activity can be an opportunity or a threat. Implication: Prices negotiated during sales call activity can be an opportunity or a threat. The asking price can be above the contract price. However, it can also be a threat because the asking price is higher than the standard room price that has been determined, and it is necessary to increase promotion and advertising and develop social media as an advertising tool to ensure comfort, profit, and flexibility of booking hotel rooms to salespeople. Keywords: Hotel, Occupancy, Sales Call, Strategy.